Complex Congenital Heart Lesion - Should We Operate or Not? - Ene Claudia-Andreea; Olaru-Lego Georgiana; Coman Ioan-Mircea; Platon Pavel; Mereuță Adrian (Sciendo, 2024)
Congenitally corrected transposition of the great arteries (ccTGA) is a rare congenital anomaly defined by double discordance - atrioventricular and ventricular-arterial. ccTGA frequently has associated lesions, which influence long-term survival.